Scarring recessions and credit constraints : evidence from Colombian firm dynamics (2010)
Using a rich dataset of Colombian manufacturing establishments, we illustrate scarring effects of recessions operating through inefficient exit induced by heterogeneous credit constraints. We show that financially constrained businesses may be forced to exit the market during recessions even if they are more productive than surviving unconstrained counterparts: an unconstrained plant with TFP at the lowest 10th percentile faces the same estimated exit probability as a constrained plant with TFP at the 79th percentile. If credit constraints affect 1/3 of businesses, we estimate aggregate TFP losses of 1.2 log points after a four year long recession.